Alternative Design for Visual Identity of Yayasan Batik Indonesia - Puspita Putri Nugroho; Vera Jenny Basiroen (Bina Nusantara University, 2015)
The research objective is to create a logo as the main visual identity. It is together with the graphic elements to support the overall visual identity of the organization and also apply the corporate identity to various applications to effectively foster the professional and trustworthy image of the organization as the foundation in Indonesia aiming for preserving and advancing Batik as the national asset. The writer used qualitative and quantitative method. Qualitative method included Face-to-face interview with the vice secretary of YBI, e-mail interview with the previous logo designer and direct survey to Textile Museum Jakarta and Batik Gallery; and Quantitative method through online survey. The result of the project is a new visual identity for Yayasan Batik Indonesia, which portrays its vision and mission. Design is the core in attaining an advantageous visual identity that could portray the image of the respected organization. When a consistency is applied through the whole visual identity, professional character of the organization is achieved.